(untitled) (London Journal of Medical and Health Research, 2023)
Background: Work-related musculoskeletal disorders (WRMSDs) poses a major problem among Nurses and Laboratory technicians (LTs) today, affecting the quality of services offered, and may leads to long term disability and job abandonment. Although there is evidence that many Nurses and LTs suffer from WRMSDs, there is no sufficient data on its prevalence, possible risk factors and the coping strategies at the LDHD and NDHD, 4th category hospitals in the city of Douala, Cameroon. Objective: To determine the prevalence, occurrence of associated factors and the coping strategies of WRMSDs among Nurses and LTs at the LDHD and NDHD. Methods: This was a cross-sectional study conducted in four 4th category hospital in Douala from February to April 2023. A total of 250 questionnaires were distributed to LTs and Nurses who gave their consents to participate in the study, 155 returned the questionnaires, giving a response rate of 62%. A total of 81 nurses and 74 LTs participated in the study. Data on demographic characteristics, and associated factors were collected using a structured questionnaire while the Nordic questionnaire was used to obtain the prevalence of WRMSDs. Musculoskeletal pain intensity was assessed using the visual analog scale (VAS) where 0 = no pain, 1-4 = mild pain, 4-6 = moderate pain, and 7-10 = severe pain. The data collected was entered into Microsoft excel, verified for consistency then analyzed using SPSS version 23.0. Descriptive statistics was used to present the results on tables and figures, while statistical analysis was set at p < 0.05. Results: The overall prevalence of WRMSDs among nurses and LTs was 78.7% (122/155). The prevalence of WRMSDS among Nurses and LTs was at 90.1% and 66.2% respectively. The neck upper (31.0%) and lower back (29.6%) were the most affected body regions reported in this study. With respect to the intensity of pain, majority (35%; 55/155) reported having severe pain within the past 7 days. Working above eight hours per day was significantly associated (?2 = 4.054; p = 0.044) with WRMSDs, while doing repetitive task (80.6 %), one working shift (81.5%), standing for long (75.0%), and sitting for long (75.0%) were common among nurses and LTs, but not significantly associated with WRMSDs in the study. The main coping strategies were; regular exercises (74.2%), praying and believing in God for healings (83.2%), relying on pain pills (57.4%), and taking off days from work (52.3%). Conclusion: The prevalence of WRMSDs was high among Nurses and LTs practicing in LDHD and NDHD, and nurses were the most affected. The neck, upper and lower back were more affected than other body regions. Working for more than 8 hours a day, doing repetitive task, one working shift and maintaining prolonged positions were identified as associated factors of WRMSDs. Regular exercises, praying and believing in God for divine healings, relying on pain pills, and taking off days from work were the major coping strategies applied.